The real effects of judicial enforcement - Vincenzo Pezone (Leibniz Institute for Financial Research SAFE, 2020)
This paper shows that judicial enforcement has substantial effects on firms' decisions with regard to their employment policies. To establish causality, I exploit a reorganization of the court districts in Italy involving judicial district mergers as a shock to court productivity. I find that an improvement in enforcement, as measured by a reduction in average trial length, has a large, positive effect on firm employment. These effects are stronger in firms with high leverage, or that belong to industries more dependent on external finance and characterized by higher complementarity between labor and capital, consistent with a financing channel driving the results. Moreover, in presence of stronger enforcement, firms can raise more debt to dampen the impact of negative shocks and, in this way, reduce employment fluctuations.
Keywords: G30; K42; D25; 330; Law Enforcement; Duration of Civil Proceedings; Financing Constraints; Finance and Employment